(3fSje GdQjGV aj TQM TaGA GdbGVi YjGVs - (3CMeO Hf eMeO Hf YeQ, TgGH GdOjf GdNaGLj GdeUQj , GdTgGH GdNaGLj,J (B1069 (3g` s; (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi fhQ GdNGabjf HHYKI GdfhQ GdeHjf , hLYdgG TaGA deG ai GdUOhQ SejJg fSje GdQjGV ai TQM TaG GdbGVi YjGV s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg bhdg (B: (3hcGf QShd Gddg Udi Gddg Ydjg hSde (B:(3CHYO GdfGS ZVHkG hCSQYge QVi , Ci ZVjI HYjO hai GdMOjK GdeDef HWF GdZVH , SQjY GdQVi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG JedcGJ efgG SfI (B1127 (3g`s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs